Supply Chain Sustainability Risk Assessment to Support Supply Chain Resilience Improvement Using House of Risk (HoR) and Interpretive Structural Modeling (ISM) at PT XYZ - Qhintara Wahyono (EPI International Journal of Engineering, 2025)
Supply chain activities in the shipbuilding industry have high complexity, which may generate sustainability risks and affect the company’s supply chain resilience. This study aims to assess sustainability risks in the supply chain and formulate mitigation strategies toward supply chain resilience at PT XYZ. The methods employed in this study are House of Risk and Interpretive Structural Modeling. The analysis results identified 24 risk events and 30 risk agents, with additional works as the main priority risk agent having an Aggregate Risk Potential value of 945. The most effective mitigation strategy identified is project coordination meetings based on a master schedule, with an Effectiveness to Difficulty Ratio value of 3,846.67. The results of Interpretive Structural Modeling indicate that knowledge, visibility, risk management culture, and trust are the main driving elements in supporting the company’s supply chain resilience. Based on the synthesis of both analyses, mitigation strategies are focused on improving planning, cross-divisional coordination, and organizational learning across three phases: pre-disruption, during disruption, and post-disruption. This study is expected to provide strategic recommendations to support the strengthening of the company’s supply chain resilience.